2012
DOI: 10.1063/1.4754134
|View full text |Cite
|
Sign up to set email alerts
|

Transparent p-type AlN:SnO2 and p-AlN:SnO2/n-SnO2:In2O3 p-n junction fabrication

Abstract: Black silicon with controllable macropore array for enhanced photoelectrochemical performance Appl. Phys. Lett. 101, 111901 (2012) Band offsets in ZrO2/InGaZnO4 heterojunction Appl. Phys. Lett. 101, 093508 (2012) Band alignment of a carbon nanotube/n-type 6H-SiC heterojunction formed by surface decomposition of SiC using photoelectron spectroscopy Appl. Phys. Lett. 101, 092106 (2012) pn-control and pn-homojunction formation of metal-free phthalocyanine by doping AIP Advances 2, 032145 (2012) Additional info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Searching for exact solutions of nonlinear PDEs plays an important role in the study of these physical phenomena and gradually becomes one of the most important and significant tasks. In recent years, many direct methods for obtaining exact solutions of nonlinear PDEs have been presented, such as the tanh-function method [1][2][3], the homogeneous balance method [4], the sine-cosine method [5], the Jacobi elliptic function expansion method [6][7][8], the F -expansion method [9][10][11], the auxiliary equation method [12][13][14], and the exp-function method [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Searching for exact solutions of nonlinear PDEs plays an important role in the study of these physical phenomena and gradually becomes one of the most important and significant tasks. In recent years, many direct methods for obtaining exact solutions of nonlinear PDEs have been presented, such as the tanh-function method [1][2][3], the homogeneous balance method [4], the sine-cosine method [5], the Jacobi elliptic function expansion method [6][7][8], the F -expansion method [9][10][11], the auxiliary equation method [12][13][14], and the exp-function method [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, when TCOs are used as p-type and n-type defects easily form at the interface between the p-type TCOs and n-type TCOs, and they act as parallel resistances in the p-n junction, causing severe leakage current and a low turn-on voltage 20,21,[39][40][41][42]. The low leakage current and the turn-on voltage (3.24 V) approaching the bandgap of SnO 2 indicated that the defect level at the p-type AlN-doped SnO 2 /n-type fluorine-doped SnO 2 junction was low.…”
mentioning
confidence: 99%
“…With a large mass, charmonium evolutions in the hot medium can be described by a classical Boltzmann transport equation. It has described well hadroproduced charmonium R AA (N p ) at different colliding energies from SPS to LHC [15,42,43], mean transverse momentum square p 2 T (N p ) [44], and rapidity distribution R AA (y) [16]. The transport equation for hadroproduced charmonium with cold and hot nuclear matter effects is…”
mentioning
confidence: 99%
“…F gΨ is the flux factor. Charmonium decay rate in QGP is proportional to the gluon thermal density f g (k, T ) and also their inelastic cross sections σ gΨ (T ) [44]. The cross section for gluon dissociation in vacuum σ gΨ (0) can be derived through the operator production expansion.…”
mentioning
confidence: 99%